The Melatonin Treatment Improves the Ovarian Responses After Superstimulation in Thai-Holstein Crossbreeds Under Heat Stress Conditions - Ratchamak, Ruthaiporn; Thananurak, Pachara; Boonkum, Wuttigrai; Semaming, Yoswaris; Chankitisakul, Vibuntita (Frontiers in Veterinary Science, 2022)
The effect of heat stress with melatonin treatment on the superovulatory responses and embryo characteristics in Thai-Holstein crossbreds under heat stress conditions was examined. Six non-lactating cows (replication = 4; n = 24) were assigned to one of 2 treatments in double cross-over design. All cows were superstimulated with traditional treatment. Melatonin group (n=12): cows received intramuscularly injection 18 mg./50 kg. simultaneously with GnRH injection, while those in the control group (n=12) received none. Bloods samples were taken to determine lipid peroxidation (MDA) and the activity of the antioxidant enzymes (superoxide dismutase; SOD). The experiment was conducted from April to September, which determined severe heat stress (the mean temperature-humidity index above 77). The results revealed that numbers of large follicles and corpora lutea were higher in the melatonin group than in the control group (p<0.01). Numbers of recovered ova/embryos, fertilized ova, and transferable embryos were higher in the melatonin group (p<0.01); meanwhile, more degenerated embryos were found in the control group (p<0.01). Increased activity of the antioxidant enzymes SOD after melatonin administration decreased MDA levels (p<0.05). In summary, melatonin administration benefited the ovarian response and embryo quality in superstimulated Thai-Holstein crossbreed affected by heat stress.